COPD and lung cancer incidence in the Women's Health Initiative Observational Study: A brief report. (March 2020) - Nagasaka, Misako; Lehman, Amy; Chlebowski, Rowan; Haynes, Brittany M.; Ho, Gloria; Patel, Manali; Sakoda, Lori C.; Schwartz, Ann G.; Simon, Michael S.; Cote, Michele L.
Highlights: This analysis of 92, 000 women included 1536 who developed lung cancer. Women who self-reported COPD were 1.6 times more likely to develop lung cancer. The association between COPD and lung cancer was similar across tumor subtypes. Abstract: Objectives: Lung cancer is the leading cause of cancer mortality in both men and women in the United States. COPD is associated with lung cancer independently of cigarette smoking, but remains understudied in women. Utilizing data from the Women's Health Initiative Observational Study (WHI-OS), this report investigates the association between COPD and development of lung cancer, with a focus on ethnicity and cancer subtype. Materials and methods: The WHI-OS, part of the larger Women's Health Initiative (WHI), is comprised of postmenopausal women between ages 50 and 79 years old at enrollment. Self-administered questionnaires were utilized to gather baseline demographic, socioeconomic, and behavioral information from participants. For this analysis, COPD status was determined at study entry (baseline) and on annual survey (incident). Information on the primary outcome of interest, diagnosis of lung cancer, was also collected annually. Results and conclusion: Of the 92, 789 women examined, 1, 536 developed lung cancer. Overall, women with COPD were 1.64 times more likely to develop lung cancer than those without COPD, after adjusting for smoking status and intensity, ethnicity, education, body mass index, and income (HR = 1.64, 95 % CI: 1.43, 1.89). The relationship between COPD and lung cancer was not found to be significantly different between ethnic groups (p-value = 0.697). The associations between COPD and lung cancer was similar across subtypes (HR range 1.31–2.16), after adjusting for smoking status and intensity. COPD increases risk of lung cancer in women, thus they may benefit from more intensive surveillance compared to similar women without COPD.